Exploring Personality Traits in Elite Sport Players and Associate with a Good Project Managers - Kateřina Bočková; Slávka Čepelová (Ital Publication, 2023)
The paper deals with the issue of personality in the context of the professions of an elite tennis player and a project manager. The objective of the conducted research is to find a set of personality characteristics typical for tennis and project management and to find out which personality characteristics of the analyzed professions are similar, or different. To confirm the hypothesis H: